2012
DOI: 10.1007/s00127-012-0531-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress and development of depression and heavy drinking in adulthood: moderating effects of childhood trauma

Abstract: Childhood trauma increases risk for both depression and heavy drinking. Trauma may moderate the effect of stress on depression; the relationship among trauma, stress and heavy drinking is less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
2
25
2
Order By: Relevance
“…This suggests that stress exposure could increase the risk of consuming more alcohol among previous regular users consistent with reviews on the effect of stress on continuation of alcohol use (162). On the other hand, some studies reported no relationships between stressful events and drinking patterns: recent life stress did not predict drinking patterns when also accounting for childhood trauma (143) or sex (146); this latter study found stressful events to relate to more heavy drinking in men, whereas in women more heavy drinking related to stressful events only in those with a history of childhood trauma.…”
Section: Effects Of Trauma or Stress On Stages Of The Addiction Cyclecontrasting
confidence: 64%
See 2 more Smart Citations
“…This suggests that stress exposure could increase the risk of consuming more alcohol among previous regular users consistent with reviews on the effect of stress on continuation of alcohol use (162). On the other hand, some studies reported no relationships between stressful events and drinking patterns: recent life stress did not predict drinking patterns when also accounting for childhood trauma (143) or sex (146); this latter study found stressful events to relate to more heavy drinking in men, whereas in women more heavy drinking related to stressful events only in those with a history of childhood trauma.…”
Section: Effects Of Trauma or Stress On Stages Of The Addiction Cyclecontrasting
confidence: 64%
“…Childhood trauma increases risk to develop a substance use disorder (1215, 1720, 23, 78, 86, 93, 143, 144), including for nicotine, alcohol, marijuana, stimulants, sedatives, and opioids, but not cocaine (120). In addition, a history of childhood sexual, physical, or emotional abuse was related to heavier or more frequent alcohol or substance use in adults across substance use disorders (22, 88, 93), although other studies did not find this (89).…”
Section: Effects Of Trauma or Stress On Stages Of The Addiction Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Using similar definitions as previous studies using NPHS data, 17 we defined several types of stressors: childhood trauma, recent marital problems, recent unemployment, recent household financial problems, work stress, chronic stress and change in social support. Childhood trauma was assessed in Cycle 1 (1994/1995) for those 18 or older at that time, and in Cycle 4 (2000/2001) for the rest of our cohort.…”
Section: Stressorsmentioning
confidence: 99%
“…For example, it increases the risk of psychiatric disorders such as depression [1,[3][4][5], bipolar disorder [6], post-traumatic stress disorder [1,4] and suicide attempts [1,4], as well as alcohol use disorder (AUD) [1,3,7,8]. The prevalence of traumatic experiences in childhood has been found to be very high in patients with AUD.…”
Section: Introductionmentioning
confidence: 99%